2019
DOI: 10.1103/physrevb.99.115202
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic suppression of Auger recombination in Weyl semimetals

Abstract: Auger recombination (AR) being electron-hole annihilation with energy-momentum transfer to another carrier is believed to speed up in materials with small band gap. We theoretically show that this rule is violated in gapless three-dimensional materials with ultra-relativistic electron-hole dispersion, Weyl semimetals (WSM). Namely, AR is prohibited by energy-momentum conservation laws in prototypical WSM with a single Weyl node, even in the presence of anisotropy and tilt. In real multi-node WSM, the geometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…The lifetime is of the order of 100 fs in graphene, however, we should note that there are other trARPES reports that do not show any population inversion in graphene within the temporal resolution of the experiment . In 3D TIs, the lifetime is extended to at least several ps in recent reports Suppression of Auger scattering that was theoretically predicted to occur in WSMs, could lead to population inversion with similar lifetimes …”
Section: General Theory Of Pumped Dmsmentioning
confidence: 68%
See 3 more Smart Citations
“…The lifetime is of the order of 100 fs in graphene, however, we should note that there are other trARPES reports that do not show any population inversion in graphene within the temporal resolution of the experiment . In 3D TIs, the lifetime is extended to at least several ps in recent reports Suppression of Auger scattering that was theoretically predicted to occur in WSMs, could lead to population inversion with similar lifetimes …”
Section: General Theory Of Pumped Dmsmentioning
confidence: 68%
“…A recent theoretical work suggested that population inversion could be also realized in 3D DMs . It was shown that ultrarelativistic electronic dispersion of WSMs leads to strong suppression of Auger recombination due to phase space restrictions imposed by energy and momentum conservation.…”
Section: Discussion and Experimental Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Естественно, что наиболее остро проблема ОР встает в случае отсутствия энергетической щели как таковой. Однако, в недавно открытых материалах с ультрарелятивистским законом дисперсии носителейполуметаллах Вейля (ПМВ) [1] -ОР может быть сильно (на несколько порядков) подавлена [2]. В случае строго изотропного закона дисперсии или наличия единственной точки Вейля во всей зоне Бриллюэна процесс ОР оказывается запрещенным законами сохранения, а его интенсивность в пределе малого дополнительного рассеяния стремится к нулю (в отличие от графена [3]).…”
Section: Doi 1034077/semicond2019-489unclassified